The Use of Postoperative Restraints in Children after Cleft Lip or Cleft Palate Repair: A Preliminary Report. (22nd January 2013) - Huth, Jennifer; Petersen, J. Dayne; Lehman, James A.
Abstract : Purpose . This study examines whether the use of elbow restraints after cleft lip/palate repair has a relationship to postoperative complications. Methods . A comparative descriptive design was used to study a convenience sample of children undergoing repair of cleft lip/palate at Akron Children's Hospital with Institutional Review Board approval. The children were randomized into intervention or control groups with use of elbow restraints considered the intervention. The study consists of two arms; one examined children after cleft lip repair, the second examined children after cleft palate repair. Repairs were performed by a single surgeon. Data collected included age, comorbidities, patient discomfort measured by pain score, frequency and duration of pain medications, use of pacifier or finger/thumb sucking, and postoperative complications including disruption of the suture line. Results . With 47 post palate repair patients and 47 post cleft repair patients, there is no significant difference (P > 0.05 ) in the occurrence of postoperative complications. Conclusions . Study results provide prospective evidence to support postoperative observation of children by surgery staff and family following cleft lip or cleft palate repair without the use of elbow restraints. Clinicians should reevaluate the use of elbow restraints after cleft lip/palate repair based on the belief restraints prevent postoperative complications.